518 Efficacy and Safety of Embolo-Sclerotherapy of Low-Flow Vascular Malformations Based on the Experience from a Single Specialist Centre. (19th August 2022) - Pang, C; Arasakumar, D; Evans, N; Papadopoulou, A; Khalifa, M; Hamilton, G; Brookes, J; Lim, CS
Abstract: Aim: To evaluate the efficacy and safety of embolo-sclerotherapy (EST) of low-flow vascular malformations (LFVM) in a specialist vascular anomalies centre. Method: All patients with LFVM who underwent EST from 01 January 2015–31 December 2019 were retrospectively reviewed. All ESTs were performed with foam STS 3%, ethanol, coils and/or other substances e.g., triamcinolone. LFVMs were grouped according to Puig's classification. The outcome measures were treatment effects and complications. Continuous variables were compared using analysis of variance (ANOVA) F test. Other discrete variables were compared using Chi-squared tests. P<0.05 were considered significant. Results: A total of 207 patients, with a mean age of 32 years (range 1–71 years) were included. The use of EST with foam STS was significantly lower for type I LFVM (61.8%) compared to others (p<0.001). However, significantly higher type I LFVM (26.5%) were treated with surgery than EST (p<0.001). Overall, outcome categories were significantly different across all types of LFVM (p<0.001), with more discharges for Type I (52.9%) LFVMs but more failure to follow-up in patients with Type II (24.5%) LFVM. EST complications was significantly higher with type I (14.7%) LFVMs (p=0.030). The doses of STS in the first procedure were significantly different across all types of LFVM (p<0.001) with most type I LFVM patients receiving ≤2ml. Conclusions: EST particularly with foam sclerotherapy is clinically effective and safe for patients with LFVM especially in those with Puig's type I and II lesions. This classification may provide an important guide to volume of sclerosant required and the potential success rate.